Lessons unlearned : the U.S. Army's role in creating the forever wars in Afghanistan and Iraq - Proctor, Pat, 1971- (American military experience series., 2020)
"Pat Proctor has written an important, long overdue, critique of the Army's preparation and outlook in the all-volunteer era. As a soldier-scholar, his book contributes an original argument on a national security issue that continues to vex in the twenty-first century: Has the Army lost its ability to win strategically by focusing on fighting conventional battles against peer enemies, or can it adapt to deal with the greater complexity of counterinsurgent and information age warfare? In this blunt critique of the senior leadership of the U.S. Army, Colonel Proctor reveals that after the fall of the Soviet Union, the U.S. Army stubbornly refused to reshape itself in response to this new strategic reality, leaving it largely unprepared when the wars in Afghanistan and Iraq began. This is the first study to connect the failures of these wars to America's disastrous performance in the war on terror. Moreover, this book is not just an esoteric history; the U.S. Army is marching headlong toward repeating the same mistakes. This book serves as an "intervention," an attempt to convince Army leaders to change what Colonel Proctor contends is a disastrous course"--